OBSERVACIONES SOBRE ENTOMOFAUNA DE SUELO Y FOLLAJE EN LA RESERVA NACIONAL RIO CLARILLO, REGION METROPOLITANA, CHILE (Acta Entomológica Chilena, 2022)
The entomofauna of foliage and soil surface is studied at the Reserva Nacional Río Clarillo, RegiónMetropolitana de Santiago, Chile. The samples were taken during spring time in two slopes of polarand equatorial orientation respectively, in relation with the plants species that characterize eachsituation. A list of species collected in foliage and soil surface is provided. A great dissimilarity betweenthe insect fauna of both ecological situations is recognized and a scarce insect-plant relationship ispostulated. The temporal fluctuations of the insects communities of soil and foliage are compared; thesoil surface fauna changes are probably associated with the microclimatological conditions of the soilsurface, while the foliage fauna changes are related to the phenological situation of plants. Finaly, aslope effect is recognized in soil surface fauna not present in the foliage one.